2010
DOI: 10.2174/1874364101004010039
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Sensitivity in Patients with Beta-Thalassemia Major and Sickle Cell Disease Under Regular Transfusions and Treatment with Desferrioxamine

Abstract: Purpose: Evaluation of contrast sensitivity in patients with beta-thalassemia major and sickle cell disease which undergo regular transfusions and chelation therapy with desferrioxamine (DFX).Materials and Methods:We studied contrast sensitivity in 48 eyes (24 patients) with beta-thalassemia major (group A) and in 42 eyes (21 patients) with sickle cell disease (group B), compared to 60 eyes of 30 healthy individuals (control group). Contrast sensitivity was measured using B-VAT II-SG Mentor Video Aquity Tester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Previous studies have also confirmed similar findings; Gartaganis et al have found that contrast sensitivity function in all beta-thalassemic patients with normal Snellen visual acuity was significantly lower compared to the normal control subjects for all spatial frequencies tested 10 . Spyridon et al also reported reduced contrast sensitivity values in patients with major thalassemia than the values for normal subjects for frequencies of 2, 3 and 6 cpd 11 …”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies have also confirmed similar findings; Gartaganis et al have found that contrast sensitivity function in all beta-thalassemic patients with normal Snellen visual acuity was significantly lower compared to the normal control subjects for all spatial frequencies tested 10 . Spyridon et al also reported reduced contrast sensitivity values in patients with major thalassemia than the values for normal subjects for frequencies of 2, 3 and 6 cpd 11 …”
Section: Discussionsupporting
confidence: 58%
“…Ocular complications of thalassemia and its therapeutic modalities has been reported by many sources 1, 3, 7, 8. But there are only few studies that evaluate contrast sensitivity in these patients 9, 10, 11. Impaired contrast sensitivity in the presence of normal visual acuity can detect early changes in the visual system of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] The high dosage required for treatment can lead to deterioration in vision, cardiac health and overall growth. [13, 14] It has been speculated that some of the side effects of chelation therapy may be the result of off-target metal binding by the administered drug that leads to deficiency in other essential metals. [15] While one DFO molecule provides sufficient donor atoms to fill the six coordination sites of iron and form stable non-reactive complexes, it can also bind other metal ions.…”
Section: Introductionmentioning
confidence: 99%